(untitled) (Journal of Universal Science Research, 2023)
Today, the pharmaceutical market of Uzbekistan presents the products of manufacturers from 90 countries of the world, many domestic manufacturers, in turn, are planning or have already established the export of their products. In this regard, the pre-registration examination of drug names should be based on the methodological and organizational principles adopted in international practice, and, above all, the regulatory agencies of countries with a high level of development of pharmaceutical legislation.